Common thrombophilia markers in young patients with primary arterial and venous thrombosis - Gupta, Monika; Kathuria, Megha; Marwah, Nisha; Sen, Rajeev (International Journal of Research in Medical Sciences, 2016)
Background: The pathogenesis of vascular thrombotic event involves an interaction of multiple genetic and environmental factors. Genetic factors include activated protein C resistance, deficiency of natural anticoagulants protein C, protein S, factor V and antithrombin III while acquired cause include presence of antiphospholipid antibody. This study was carried out to establish the role of basic panel of thrombophilia in diagnosing the patients with primary thrombophilia. Methods: A total of 121 consecutive patients with history suggestive of arterial or venous thrombosis were included. History of risk factors including smoking, hypertension, hyperlipidemia, diabetes mellitus and family history of thrombosis were elicited. The initial tests included CBC, PT, APTT, LFT, blood sugar and lipid profile. Functional assay on thrombophilia markers were performed by means of clotting based method. Results: A total of 121 patients were studied, out of which 63 were males and 58 females. The mean age range was 15-40 years. No abnormality was detected in 75 samples, while 46 samples (38%) were positive for one or more thrombophilia markers, of which 6 had more than one thrombophilia marker. Abnormality of a single thrombophilia factor was found in 40 patients, in which two patients were also positive for lupus anticoagulant. Conclusions: An association was found between low levels of protein C, protein S and factor V and a thrombotic event. Screening of these patients using a panel of thromophilia markers can provide valuable information in primary diagnosis of inherited deficiency even in the absence of high end molecular/mutational studies.